THE COMPONENT SYSTEMS OF ECONOMIC SECURITY OF TOURIST DESTINATIONS - Moskvichova , O.S.; Buriachenko , O.V. (The actual problems of regional economy development, 2021)
The article is aimed at studying the components of the system of economic security of tourist destinations. For this purpose, the economic indicators of tourism development in Ukraine and the world were analyzed, as well as expenditure items of the state budget of Ukraine, their distribution between direct and indirect components of the tourism industry and their dynamics. The necessity of transformation of the Ukrainian sphere of tourism in order to popularize the state as a world-class tourist destination and increase the flow of tourists is proved. The components of the system of economic security of Ukraine as a tourist destination have been established. The purpose of the article is to form a system of economic security of the tourist destination in the system of uncertainty of the national economy. The methodological basis of the study are general and special methods of cognition, research literature, scientific works of domestic scientists on economic security of tourist destinations, especially in conditions of uncertainty of the national economy, as well as other methods such as systems analysis; synthesis, statistical method and others. The scientific novelty lies in the analysis of economic indicators of tourism development in Ukraine and the world, as well as the analysis of expenditure items of the state budget of Ukraine, their distribution between direct and indirect components of the tourism industry and their dynamics. The practical significance of the article lies in the proposals for public administration of the tourism industry of Ukraine, which consists of four subsystems that interact with each other (political, economic, natural and social), as well as aimed at sustainable development of economic security and tourist destinations in particular. The functioning of the economic security system of a tourist destination should be ensured by all facilities and under the close supervision of public authorities.